Timing effects of short-term smoking cessation on lung cancer postoperative complications: a systematic review and meta-analysis - Zhan Zhang; Yue Zhao; Jianhao Qiu; Zhenyi Li; Lin Li; Hui Tian (World Journal of Surgical Oncology)
Abstract Background Preoperative smoking cessation may reduce postoperative complications in patients with lung cancer. However, the optimal duration of short-term preoperative smoking cessation remains unclear. Methods Three databases, PubMed, Embase, and the Cochrane Library, were searched for studies published up to April 5, 2024. The Newcastle–Ottawa scale was used to assess the risk of bias. The included studies compared the incidence of postoperative complications between patients with different preoperative smoking cessation times and those with persistent preoperative smoking. A meta-analysis of postoperative complications and events such as pneumonia was performed in patients with lung cancer. Results Fourteen studies met the inclusion criteria and included a total of 50,741 patients who had undergone pulmonary resection. The meta-analysis showed that preoperative smoking cessation of > 2 weeks and < 1 month did not reduce the incidence of postoperative complications (odds ratio [OR] 1.05; 95% confidence interval [CI] 0.76–1.44; P = 0.78) and pneumonia (OR 0.98; 95% CI 0.60–1.61; P = 0.95). Moreover, preoperative smoking cessation for > 1 month was effective in reducing the incidence of postoperative complications (OR 0.72; 95% CI 0.63–0.83; P < 0.01) as well as pneumonia (OR 0.80; 95% CI 0.49–1.33; P = 0.40). Conclusions This meta-analysis suggests that preoperative smoking cessation for > 1 month is effective in reducing complications and pneumonia after pulmonary resection in patients with lung cancer, especially as video-assisted thoracoscopic surgery (VATS) and robotic-assisted surgery become more common.